Pattern and Distribution of Fatal Injuries in Road Traffic Accidents at Udaipur (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
The term accident has been defined as an occurrence in a sequence of events, which usually produces unintended injury, death or property damage. Today, accidents are among the leading causes of death, in some cases the foremost cause. This study is having a lot of importance in this Udaipur region, as this area is very hilly, having most of the population as tribes, congested and important national highways, a lot of mines, marble industries, India’s prime tourist locations, a lot of beautiful lakes, low education level in general population, use of two-wheelers in maximum extent by farmers and labourers in their daily routine livelihood works, hard geographical conditions, high rainy areas that makes the transportation quite difficult, faulty roads, primary and secondary referral centres with inadequate resources and manpower and most important factor that makes this area very vulnerable for fatal road traffic accidents is low awareness level regarding traffic rules, regulations and civic sense in general population.
Keywords: Laceration; Road Traffic Accidents; Regional Injuries; Fatal Injuries